Motivation in medical students: higher intrinsic motivation among graduate-entry students across academic stages - Matos Sousa, Rita; Santos, Maurílio; Marangoni, Marco; Pereira, Vitor Hugo (Frontiers in Medicine, 2025)
Academic success and professional development are determined by several factors, being motivation an important one. In this study we explored its different dimensions of motivation among students enrolled in the undergraduate medical degree at the School of Medicine of the University of Minho, comparing students from the traditional national entry and graduate entry (PA) pathways across all curricular years. A total of 354 students (response rate: 39.4%) participated in this cross-sectional study during the 2023/2024 and 2024/2025 academic years. Motivation was assessed using the Minho Medical Academic Motivation Scale—Minho-MEDAMS, a validated scale adapted within the Self-Determination Theory framework. Motivation types examined included intrinsic motivation (IM), identified regulation (EMID), introjected regulation (EMIR), external regulation (EMER), and amotivation (AMOT), alongside the Self-Determination Index (SDI). Statistical analyses were conducted to compare motivation across academic years, entry pathways, gender, and age groups. EMID and IM were the most prevalent motivation types, while AMOT was the least reported. No significant differences were found in motivation levels across academic years. PA students showed significantly higher levels of IM, EMID, and SDI compared to traditional pathway students. Motivation levels did not vary significantly with age, and gender differences were minimal, with the exception of higher EMER scores among male students. In conclusion, these findings suggest that graduate-entry students are more self-determined in their motivation profiles, independent of age, and that motivation remains relatively stable throughout the medical curriculum.